Interview to Maria Lúcia Garcia Pallares-Burke - Pallares-Burke, Maria Lúcia Garcia (Tempo Social, 1998)
In this interview, Anthony Giddens speaks about contemporary problems of the social sciences and their relationship with Latin America and Brazil.